FAKTOR MAKRO EKONOMI TERHADAP NILAI EKSPOR NON MIGAS - ERICHA PERMATASARI; FIRSTY RAMADHONA AMALIA LUBIS (JURNAL ILMIAH KOHESI, 2022)
Indonesia has an engine of economic growth that comes from oil and gas exports and non-oil and gas exports which are sectors that can affect the Indonesian economy. The aim is to analyze how long-term and short-term macroeconomic factors influence, namely Interest Rates, Inflation, WPI Index, Exchange Rate on Non-Oil and Gas Exports. The data used is a time series and data taken from 2009 to 2019 and sourced from the official website of Bank Indonesia (BI) and the Central Statistics Agency (BPS). The data obtained was processed using the Eviews 9 analysis tool and the method used is the Vector Error Correction Model (VECM) method. The test results show different effects in the long and short term for interest rate variables, inflation, Wholesale Price Index, Exchange Rate on Non-Oil and Gas Exports.